Penile Circular Fasciocutaneous (McAninch) Flap as an Option for Complex Anterior Urethral Stricture in Case of Non-Viable Buccal Mucosal Graft - Vijayganapathy, Sundaramoorthy (J Clin Diagn Res, 2016)
The penile circular fasciocutaneous flap (FCF) is employed in the successful single stage reconstruction of long segment complex anterior urethral strictures especially when buccal mucosa is unavailable due to various reasons. A 65-year-old gentleman, chronic smoker and tobacco chewer, hypertensive on treatment, presented with obstructive lower urinary tract symptoms for 8 months. He had no prior urethral catheterization. On examination, he had circumcised penis, with stenosis of the external urethral meatus. Glans had no changes suggesting balanitis xerotica obliterans. Suprapubic cystostomy was done as he developed acute urinary retention during evaluation. Retrograde urethrogram (RGU) showed pan-anterior urethral stricture. He was planned for substitution urethroplasty. On oral cavity examination, he had moderate trismus with oral submucous fibrosis. As buccal mucosal graft was unavailable, he was planned for FCF. A ventral onlay tubularization FCF urethroplasty from meatus to bulbar urethra based on dartos dorsal pedicle was done. His postoperative recovery was uneventful. Pericatheter RGU did not show extravastion and he voided well with Qmax 14 ml/second. He is doing well at follow-up.